Exonerating Eve: - S M Mahfuzur Rahman (Crossings, 2020)
For millennia, women have been demonized and denigrated through the metanarrative of Eve’s collaboration with Satan in Paradise as proof of women’s inherent moral inferiority as the progenitors of the “Original Sin.” Grandstanding poets such as Milton with their grandiose epics such as Paradise Lost have perpetuated and propelled the myth of the “second sex.” Thus, one half of humanity has been condemned and confined to their “place” indoors and reduced to the service of the “superior sex” – until the revolutionary age of the Romantics attacked all grand narratives. The two Brontë sisters, Charlotte and Emily, for instance, tried to upend the narrative of subjugation by championing the egalitarian struggle of Eve and Lucifer over the hierarchical order of Adam and God. The subversive strategy of delegitimizing the metanarrative of the Original Sin frequents in Shirley and haunts the gothic landscapes of Jane Eyre and Wuthering Heights, where the female central characters, Jane and Cathy respectively, undercut and undermine their feminine performativity by bending the will of their male counterparts. Deconstructing the abovementioned novels, this paper aims to demonstrate how the Brontë sisters actually attempted to unravel the metanarrative of the Fall from within – to hail Eve as the genuine “hero” – and prove how the feminine intellect is at par, if not superior, to that of the masculine.